P1.19 High-throughput identification of sexually transmitted infections and bacterial vaginosis associated pathogens on openarray™ nanofluidics qpcr platform in south africa. (8th July 2017) - Norman, Emily; Dewulf, Dominique; Maseko, Venessa; Bradfield, Joanne; Patel, Sunali; Naicker, Nivashnee; Samsunder, Natasha; Jacobs, Peter; Garrett, Nigel
Abstract : Introduction: Cheap and efficient pathogen detection solutions are required to replace syndromic STI management in low and middle income countries. One solution may be point-of-care technologies at clinic level, another could be centralised high-throughput technologies. ThermoFisher recently launched the TaqMan Vaginal Microbiota Assays, in combination with OpenArray Nanofluidics qPCR platform, which is capable of testing 192 samples for 34 individual STI and bacterial vaginosis (BV) pathogens in a 2 hour qPCR run. The goal of this study was to evaluate OpenArray against an established multiplex PCR assay, and further optimise its workflow. Methods: Evaluation of the TaqMan Vaginal Microbiota assays on OpenArray platform was performed for 50 vaginal micobiota vaginal swab samples that had been characterised for N. gonorrheae (NG), C. trachomatis (CT), and T. vaginalis (TV) on an established CDC-approved multiplex PCR assay. Blind samples were provided for testing on the OpenArray platform. Nugent scores were obtained in parallel to molecular testing and results were compared for 11 specific bacterial strains indicative of BV. Results: High specificity (97.4%–100%) was observed at initial testing of STI samples, however the sensitivity was not as expected (NG 81.8%, CT 38.5%, TV 50.0%) due to concentrations of STI pathogens below the limit of detection on OpenArray, which was confirmed by 384-well plate testing (CRT range 33–38). Pre-amplification of STI samples improved the sensitivity significantly (NG 100%, CT 92%, TV 82%). Nugent scores for 46/50 samples were compared with the qPCR results for the BV-associated targets on OpenArray. BV-associated pathogens like G. vaginalis, A. vaginae, BVAB2, Megasphaera 1, Megasphara 2, M.hominis, and M. mulieris were predominate in the samples with Nugent Scores 7–10, while commensal lactobacillus were predominate in Nugent Scores 0–3. Conclusions: After optimisation, the OpenArray Nanofluidics qPCR platform may provide a high-throughput solution for STI pathogen detection and for characterising the vaginal microbiota.